Repetitive Transcranial Magnetic Stimulation for Tinnitus Treatment in Vestibular Schwannoma: A Pilot Study - Leao, Maria Teresa; Machetanz, Kathrin; Sandritter, Joey; Liebsch, Marina; Stengel, Andreas; Tatagiba, Marcos; Naros, Georgios (Frontiers in Neurology, 2021)
Vestibular schwannomas (VS) are brain tumors affecting the vestibulocochlear nerve. Thus, VS patients suffer from tinnitus (TN). While the pathophysiology is mainly unclear, there is an increasing interest in repetitive transcranial magnetic stimulation (rTMS) for TN treatment. However, there results have been divergent. In addition to methodological aspects the heterogeneity of the patients might affect the outcome. Yet, there is no study evaluating rTMS exclusively in VS-associated tinnitus. Thus, this pilot study evaluates low-frequency rTMS to the right dorsolateral prefrontal cortex (DLPFC) in VS-associated tinnitus. This prospective pilot study enrolled nine patients with monoaural VS-associated tinnitus ipsilateral to the tumor. Patients underwent a 10-days rTMS regime (1Hz, 100% RMT, 1200 pulses, right DLPFC). The primary endpoint of the study was the reduction of TN distress (i.e., Tinnitus Handicap Inventory, THI). The secondary endpoint was a reduction of TN intensity (i.e., Tinnitus Matching Test, TMT) and the evaluation of factors predicting tinnitus outcome (i.e., hearing impairment, TN duration, type of tinnitus). No complications or side effects occurred. There was one drop-out due to non-responsiveness of the complaint. There was a significant acute effect of rTMS on the THI and TMT. However, there was no significant long-term effect after 4 weeks. While the THI failed to detect any clinically relevant acute effect of rTMS in 56% of the patients, TMT revealed a reduction of TN intensity for more than 20% in 89% and for more than 50% in 56% of the patients. Notably, the acute effect of rTMS was influenced by TN type and duration. In general, patients with a tonal TN and shorter TN duration showed a better response to rTMS therapy. The present pilot study is the first one exclusively evaluating the effect of low-frequency rTMS to the right DLPFC in VS-associated tinnitus. Our results proof the feasibility and the efficacy of rTMS in this patient cohort. There is a significant acute but limited long-term effect. In addition, there is evidence that patients with tonal tinnitus and shorter tinnitus duration might have the strongest benefit. A larger, randomized controlled study is necessary to proof these initial findings.